A Fundamental Difference: Husserl and Heidegger on the Grounding of Ethics - Nenon, Thomas (Investigaciones Fenomenológicas, 2021)
This essay begins by retracing the relationship between the early Heidegger and Edmund Husserl during the period when Heidegger’s thought was still closely aligned with Husserl’s phenomenological project. It then shows how a fundamental difference emerged over the question of what the ultimate grounds for action. When Heidegger says that Husserl has failed to address the real question about the meaning of Being, he is referring to the meaning of Dasein. Whereas Husserl maintains that willing and action must remain grounded in the intention/fulfillment structure of reason, Heidegger comes to the view that Dasein must resolutely accept its calling as the groundless ground of significance that is ulti-mate source of meaning in the world. El presente ensayo empieza retrocediendo hacia la relación del Heidegger temprano con Edmund Husserl, en el periodo en el que el pensamiento heideggeriano estaba todavía alineado con el proyecto fenomenológico de Husserl. A continuación, se muestra cómo a raíz de la pregunta por el sustrato último de toda acción emerge una diferencia fundamental. Cuando Heidegger dice que Husserl no ha conseguido hacer la verdadera pregunta acerca del sentido del ser, se refiere al sentido del Dasein. Mientras Husserl mantiene que la voluntad y la acción tienen que perma-necer fundamentadas en la estructura de intención/cumplimiento propia de la razón, Heidegger llega a la postura de que Dasein tiene que aceptar con determinación la llamada del fundamento abismático del significado, la últi-ma fuente del significado en el mundo.